Thursday

November 27, 2014

November 27, 2014

Posted by **Anonymous** on Friday, February 15, 2013 at 11:59pm.

(tanx)^(6)*(secx)^(2)

I tried splitting up tanx into (tanx)^2*(tanx)^4 and let the latter equal (secx)^2 - 1.

Please help, thanks!

**Answer this Question**

**Related Questions**

Trigonometry - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b...

Trigo - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in ...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Math - Im really struggling with these proving identities problems can somebody ...

Calc - Hello im trying to integrate tan^3 dx i have solved out the whole thing ...

Calc - Hello im trying to integrate tan^3 dx i have solved out the whole thing ...

Calculus - Integration - Hello! I really don't think I am understanding my calc ...

Trig - Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

precal- PLEASE HELP! - secx/secx-tanx=sec^2x+ secx+tanx